Administrative and legal regulation of licensing for medical practice - О. V. Batryn (Law and Safety)
The article is devoted to the peculiarities of legal regulation of licensing for medical practice. The provisions of laws and regulations governing the procedure for obtaining a licence to practice medicine are studied. The scientific works of scholars in the fields of law, medicine, and public administration who have studied legal relations in the field of healthcare and licensing are studied. Recommendations for amending the legislation are formulated.